2005
DOI: 10.1111/j.1365-2265.2005.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

Low normal TSH levels are associated with low bone mineral density in healthy postmenopausal women

Abstract: These results suggest that low normal TSH levels may not be physiological for postmenopausal women and, during treatment of hypothyroidism, may not be adequate for avoiding osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 25 publications
12
58
3
Order By: Relevance
“…This risk augments with advancing age and returns to normal upon treatment of the hyperthyroid state (9,19,20). Untreated subclinical hyperthyroidism in postmenopausal women has also been associated with decreased aBMD and a higher fracture risk compared with women who received treatment, although findings have not been unequivocal (21)(22)(23)(24). Little data exists on the influence of subclinical hyperthyroidism on the skeleton in men (5).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This risk augments with advancing age and returns to normal upon treatment of the hyperthyroid state (9,19,20). Untreated subclinical hyperthyroidism in postmenopausal women has also been associated with decreased aBMD and a higher fracture risk compared with women who received treatment, although findings have not been unequivocal (21)(22)(23)(24). Little data exists on the influence of subclinical hyperthyroidism on the skeleton in men (5).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, some authors have challenged the conventional view that skeletal responses to abnormal thyroid status result solely from altered T 3 action in the bone and have proposed TSH as a negative regulator of bone turnover (23,(33)(34)(35)(36)(37). For example, Morris et al (35) and Kim et al (23) observed associations between low-normal serum TSH levels and osteopenia and osteoporosis prevalence, together with a graded increase in aBMD with increasing TSH in postmenopausal women.…”
Section: Discussionmentioning
confidence: 96%
“…A cross-sectional study in this cohort found a lower BMD among participants with TSH !0.5 mU/l, but did not show any relation between TSH and BMD above this TSH level (31). However, some studies report a positive relation between TSH in the normal range and BMD (32,33,34), and there have even been studies that report an association between elevated TSH and low BMD (35,36).…”
Section: Discussionmentioning
confidence: 93%
“…However, 18 of the 29 examined studies considered an upper-limit TSH value of over 4 mU/l. This variability in limits might explain the lack of association between BMI and TSH in 11 (5,9,13,16,19,23,25,28,29,33,40) of the 29 examined studies. Another source of discrepancy is the fact that almost half of the studies did not perform adjustment for potential confounders.…”
Section: Discussionmentioning
confidence: 97%